2007
DOI: 10.1161/01.res.0000253487.02398.85
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Oct3/4 + Cells Differentiate Into Cardiac Myocytes via Age-Dependent Paracrine Mechanisms

Abstract: Abstract-The mechanisms that govern the capacity of the bone marrow stem cells to generate cardiac myocytes are stillunknown. Herein we demonstrate that the cardiomyogenic potential of bone marrow-derived Oct3/4 ϩ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 55 publications
(66 reference statements)
4
46
0
Order By: Relevance
“…Troponin T + cells started to form at the periphery of cell clusters after 7 days and chronotropic activity was observed after 14 days of differentiation. Importantly, efficiency of cardiac differentiation of Oct3/4 + cells declined with age (12). The differentiation pattern of BM-derived cardiomyocytes was similar to that observed in embryonic cell-derived cardiomyocytes (12,13).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Troponin T + cells started to form at the periphery of cell clusters after 7 days and chronotropic activity was observed after 14 days of differentiation. Importantly, efficiency of cardiac differentiation of Oct3/4 + cells declined with age (12). The differentiation pattern of BM-derived cardiomyocytes was similar to that observed in embryonic cell-derived cardiomyocytes (12,13).…”
Section: Discussionsupporting
confidence: 68%
“…Importantly, efficiency of cardiac differentiation of Oct3/4 + cells declined with age (12). The differentiation pattern of BM-derived cardiomyocytes was similar to that observed in embryonic cell-derived cardiomyocytes (12,13). Pallante et al confirmed that the cardiogenic Oct3/4 + cells were rare (0.05%) within BM cells localized in the osteoblastic niche.…”
Section: Discussionmentioning
confidence: 67%
“…At the same time, another independent group reported that BM cells may also be a source of Oct-4 ϩ male germ cells . Finally, as recently demonstrated, BM cells may form culture aggregates of Oct3/4 ϩ cells, which in in vitro cultures in the presence of platelet derived growth factor, may differentiate into cardiomyocytes (Pallante et al, 2007).…”
Section: Further Evidence For a Presence Of Oct-4؉ Cells In Bmmentioning
confidence: 64%
“…Stem cells that express early embryonic stem cell markers, including Oct-4, Nanog, and SSEA-1, had been identified in BM in several potential multipotent/PSC isolated from the BM or CB such as VSELs (Kucia et al, 2006b, MSC (Colter et al, 2001;Pochampally et al, 2004), MAPC (Jiang et al, 2002), MIAMI (DЈIp-polito et al, 2004), USSC (Kogler et al, 2004), and precursors of oocytes/ spermatogonia and precursors of shuttling between BM and heart cardiomyocytes (Johnson et al, 2005;Nayernia et al, 2006;Pallante et al, 2007). It is very likely that several investigators using different isolation strategies described the same populations of stem cells but gave them different names according to circumstance.…”
Section: Presence Of Oct-4 ؉ Stem Cells In the Bmmentioning
confidence: 99%
“…C-Kit, the transmembrane tyrosine kinase receptor for stem cell factor, is required for melanocyte and mast cell development, hematopoiesis and the differentiation of spermatogonial stem cells. 23 c-Kit is also transiently expressed in cardiomyocyte precursors during development and in a rare cell population in the normal adult heart. Li et al 24 demonstrated that in the heart, c-Kit is expressed not only by cardiac stem cells but also by cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%